MODERNIZATION OF MIXING SYSTEMS FOR PREPARATION OF SAND-CLAY AGGLUTINANT SANDS - D. L. Kostylev; D. M. Golub; D. M. Kukuj; A. P. Melnikov; A. I. Bachek (Литьë и металлургия, 2006)
During decades all over the world the main mixing outfits of sand-clay agglutinant sands have been blenders of periodic action of rolling type. A new generation of mixers comes to replace them